Finding Gallipoli Battlefield Remembrance and the Movement of Australian and Turkish History - West, Brad. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is about how Australian and Turkish historical understanding of the First World War Gallipoli Campaign has been shaped by travel to the battlefield for the purposes of commemoration. Utilizing a cultural historical method, the study begins with examining how cultural conceptions of travel influenced the experience of those fighting in the 1915 Battle, and ends with the way that new global insecurities and the withdrawal of Western troops from Afghanistan in 2021 is reflecting and influencing Australia and Turkey's social memory of their military past. This wide historical lens and the author's original fieldwork and analysis of documents allows for an in-depth exploration of the ways in which cultural patterns of social memory develop over time and mapping of how specific cultural representations in the past are reclaimed. The book argues that travel is a key factor influencing social change by providing distinctive ritual experiences that afford unique, discursive opportunities and empowering particular carriers and custodians of social memory.
Chapter 1: Travel Theory and Meaningful Mobility -- Chapter 2: Mobilising and Immobilising Travel -- Chapter 3: Special Anniversaries, Memorials and Travel -- Chapter 4: Tourist Pilgrimage and Reimagining the Nation -- Chapter 5: The New Tyranny of Distance and Conflict Creation. .
Keywords: Culture; Collective memory; Sociology; Sociology of Culture; Memory Studies; Sociological Theory